Obrazovanje za demokratsko građanstvo i interkulturno razumijevanje - Spajić-Vrkaš, Vedrana (2006)
The presentation focused on interrelations between education for democratic citizenship and intercultural education. Drawing form the Council of Europe’ s normative and programmatic texts, as well as from a rich theoretical literature we demonstrate that these two approaches have been brought together through a series of conceptual changes influenced by the way how societal demands and challenges were dealt with in political visions and policy development. The recent turn towards the recognition of diversity as the society’ s value and enrichment has been made possible through changes in the concepts of citizen and citizenship. Recent focus on citizenship in terms of identity formation and maintenance, on the one hand, and interpersonal and inter-group (community) relations, on the other hand, especially in the context of European integration and globalisation, has triggered profound changes in the field of education. Education for democratic citizenship facilitates these changes by opening up a space for more learner and community-oriented strategies of the exchange of knowledge and skills in the course of which different voices may be expressed. However, in order to make this possibility a sustainable European reality it is necessary to fulfil important preconditions at local and national levels, from conceptual clarification, through curricular changes and the introduction of quality assurance systems, to changes in the management of schools and teacher training. How the Council of Europe’ s programmes, projects and reference materials, especially the ones that were developed or made known in the framework of the 2005 European Year of Citizenship through Education, may inform and facilitate educational changes at different levels, is also briefly demonstrated.
Projekt MZOS
ENG